2013
DOI: 10.1093/ajh/hpt196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GLP-1 Mimetics on Blood Pressure and Relationship to Weight Loss and Glycemia Lowering: Results of a Systematic Meta-Analysis and Meta-Regression

Abstract: This meta-analysis provides evidence that GLP-1 analogs reduce sitting SBP. These findings may support potentially favorable long-term cardiovascular outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
5
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 40 publications
2
75
5
3
Order By: Relevance
“…This may be due to the small sample size of patients receiving these medications or the presence of confounding variables that distorted the association between the use of these drugs and BP control. The positive effects of these drugs on lowering BP is reported in the literature [43,44]. Therefore, this result should be investigated by r further studies.…”
Section: Discussionmentioning
confidence: 79%
“…This may be due to the small sample size of patients receiving these medications or the presence of confounding variables that distorted the association between the use of these drugs and BP control. The positive effects of these drugs on lowering BP is reported in the literature [43,44]. Therefore, this result should be investigated by r further studies.…”
Section: Discussionmentioning
confidence: 79%
“…GLP-1 receptor agonist treatment has however been associated with a small increase in heart rate [93] (Table 3, in the Appendix). A meta-analysis of 22 trials showed that GLP-1 agonists overall resulted in a significant increase in heart rate with a weighted mean difference of 1.86 beats per minute (bpm, 95% CI: 0.85-2.87) compared with placebo and 1.90 bpm (95% CI: 1.30-2.50) compared with active control (all p < 0.05) [94].…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…The cardioprotective effects of GLP-1 agonists have been well documented in pre-clinical studies. In the clinical setting, similar positive effects have been observed to various degrees in pilot studies, and the mechanism was thought to be related to reduced apoptosis and nuclear oxidative stress and improvement in myocardial glucose metabolism [46].…”
Section: Glucagon-like Peptide-1 Agonistsmentioning
confidence: 61%